A systematic review of the evaluation of endocrine-disrupting chemicals in the Japanese medaka (Oryzias latipes) fish - Dasmahapatra, Asok K.; Williams, Charmonix B.; Myla, Anitha; Tiwary, Sanjay K.; Tchounwou, Paul. B. (Frontiers in Toxicology, 2023)
Japanese medaka (Oryzias latipes) is an acceptable small laboratory fish model for evaluation and assessment of endocrine disrupting chemicals (EDCs) found in the environment. In this research, we have used this fish as a potential tool for identification of EDCs that have significant impact on human health. We conducted an electronic search in PubMed (http://www.ncbi.nlm.nih.gov/pubmed) and Google Scholar (https://scholar.google.com/) using the search terms, Japanese medaka, Oryzias latipes, and endocrine disruptions and sorted 205 articles consisting of 128 chemicals that showed potential effects on estrogen-androgen-thyroidsteroidogenesis (EATS) pathways of Japanese medaka. From these chemicals, 14 compounds, including 17β-estradiol (E2), ethinylestradiol (EE2), tamoxifen (TAM), 11-ketotestosterone (11-KT), 17β-trenbolone (TRB), flutamide (FLU), vinclozolin (VIN), triiodothyronine (T3), perfluorooctanoic acid (PFOA), tetrabromobisphenol A (TBBPA), terephthalic acid (TPA), trifloxystrobin (TRF), ketoconazole (KTC), and prochloraz (PCZ), were selected as references and used for the identification of apical endpoints within the EATS modalities. Among these endpoints, during classification, priorities are given to the sex reversal (masculinization of females and feminization of males), gonad histology (testis-ova or ovotestis), secondary sex characteristics ( anal fin papillae of males), plasma and liver vitellogenin (VTG) contents in males, swim bladder inflation during larval development, hepatic vitellogenin (vtg) and choriogenin (chg) genes in liver of males and several genes including estrogen-androgen-thyroid receptors in hypothalamuspituitary-gonad/thyroid axis (HPG/T). After reviewing 205 articles, we identified 108 (52.68%), 46 (22.43%), 19 (9.26%), 22 (17.18%) and 26 (12.68%) papers represented studies on estrogen endocrine disruptors (EED), androgen endocrine disruptors (AED), thyroid endocrine disruptors (TED), and/or steroidogenesis modulators (MOS), respectively. Most importantly, among 128 EDCs, 32 (25%), 22 (17.18%), 15 (11.8%), and 14 (10.93%) chemicals are classified as EED, AED, TED and MOS, respectively. We also identified 43 (33.59%) chemicals as high priority candidates for Tier 2 tests and 13 chemicals (10.15%) have enough potential to be considered as EDCs without any further Tier-based studies. Although our literature search was unable to identify the EATS targets of 45 chemicals (35%) studied in 60 (29.26%) of the 205 articles, our approach has sufficient strength to move the laboratory-based research data on Japanese medaka further for applications in regulatory risk assessments in humans.